Enhanced Energy Localization with Wideband Hyperthermia Treatment System - N. Nizam-Uddin; Ibrahim Elshafiey , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents a tool to enhance hyperthermia treatment based on multichannel wideband system. The potential of this system in enhancing energy localization is investigated. A model is developed for the hyperthermia treatment plan taking into account cylindrical phantom of human head. Dispersive modeling of tissue properties is used to allow wideband simulation. Problem formulation for optimization of wideband system is presented. Simplified time-delay tool based on coherent phased-array approach is developed and presented. The results reveal the potential of wideband system compared to conventional narrow band systems in enhancement of energy focus. Investigation of advanced optimization processes is introduced that allow real time shaping of the signal waveform in wideband systems. The research addresses the importance of incorporating recent techniques in processing big data to facilitate adopting wideband hyperthermia in clinical systems.